A Case Series of Intravenous Leiomyomatosis and Literature Review. Issue 1 (January 2017) - Kong, Karen K.Y.; Szabo, Rebecca A.; Pyman, Jan; Ang, W. Catarina
Intravenous leiomyomatosis (IVL) is an uncommon benign smooth-muscle tumour of the uterus which invades into uterine and systemic veins. Although benign, this tumour may grow in the absence of, or beyond the confines of a uterine leiomyoma or fibroid, and has the potential to behave aggressively via extension of growth in the venous vasculature, upwards into the inferior vena cava (IVC) and into the right cardiac chambers. This can lead to serious cardiac and pulmonary sequelae. Rarer neurological sequelae and fatal cases have also been reported. Unless there is obvious IVC or intracardiac spread on preoperative imaging, IVL poses a diagnostic challenge. IVL has been reported in the literature as a rare event and is postulated to be more common than previously reported. Potentially this change is related to increased histopathological diagnosis following hysterectomy or fibroid excision. The prognosis of the cases is unknown but requires follow up as recurrence is possible. This paper presents a case series of 12 patients who were diagnosed on post-operative histopathology with IVL in a 20-month period at The Royal Women's Hospital, Victoria, Australia and a literature review of the current management of this unusual disease.